2018
DOI: 10.1007/s00253-018-9287-8
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of activated sludge bacterial communities in two diversity variant full-scale sewage treatment plants

Abstract: Bacterial community in activated sludge (AS) is diverse and highly dynamic. Little is known about the mechanism shaping bacterial community composition and dynamics of AS and no study had quantitatively compared the contribution of abiotic environmental factors and biotic associations to the temporal dynamics of AS microbial communities with significantly different diversity. In this study, two full-scale sewage treatment plants (STPs) with distinct operational parameters and influent composition were sampled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Amarolinea” was at high abundance in the all the samples examined, which were taken in the winter (Table 4 and Supplementary Data File S1). It should also be mentioned here that Jiang et al (2018) showed it was a highly abundant filament (18% of total 16S rRNA sequences) in a foaming anoxic reactor in Hong Kong, depite the fact that it does not behave as a hydrophobic filament in situ (Andersen et al, 2019).…”
Section: Description Of the Chloroflexi Present In Activated Sludge Cmentioning
confidence: 87%
“…Amarolinea” was at high abundance in the all the samples examined, which were taken in the winter (Table 4 and Supplementary Data File S1). It should also be mentioned here that Jiang et al (2018) showed it was a highly abundant filament (18% of total 16S rRNA sequences) in a foaming anoxic reactor in Hong Kong, depite the fact that it does not behave as a hydrophobic filament in situ (Andersen et al, 2019).…”
Section: Description Of the Chloroflexi Present In Activated Sludge Cmentioning
confidence: 87%
“…Because the microbial community in the AS system in the HK_ST plant was different during sludge bulking and foaming than under normal operation (Figure S5a) and because a comprehensive temporal data set was available, an in-depth analysis was performed to investigate the shift in the community composition, assembly mechanism, and functional traits over time. Based on hierarchical k-means clustering, the microbial communities collected over a 1-year period were separated into five different phases (Figure S9a), and the sludge bulking and foaming were reported to occur in phase D. 48 Phase D showed significantly lower taxonomic and phylogenetic diversity than the other phases (Kruskal−Wallis test; p < 0.001) (Figure S9b and Figure S9c). Multinomial regressions between phase D and the other phases showed that a relatively large number of ASVs were selected for or against during sludge bulking and foaming (Table S4 and Figure S10).…”
Section: Influent Compositions Drove Microbial Communitymentioning
confidence: 99%
“…At the OTU level, the structural variation of bacterial communities across samples was visualized using the nonmetric multidimensional scaling (NMDS) based on the Bray-Curtis dissimilarity matrix. Canonical correspondence analysis (CCA) was performed to assess the effects of physicochemical factors on the bacterial communities [14]. Spearman's rank correlation was calculated to estimate the relationship between the environmental factors and relative abundances of genera [15].…”
Section: Methodsmentioning
confidence: 99%